Analisis Peluang dan Ancaman Perdagangan Internasional bagi Indonesia dengan India: Studi pada Sektor Elektronik dan Komoditas Unggulan - Tri Afrika Candra Kurniawan (CV. ITTC INDONESIA, 2026)
Indonesia's international trade with India has shown significant dynamics in recent years, particularly in the electronics sector. Indonesia's electronics exports to India surged by 168.67% in January–September 2025, making it one of the fastest-growing markets. This study aims to analyze the opportunities and threats of Indonesia-India international trade using SWOT analysis, Revealed Comparative Advantage (RCA), and Trade Complementarity Index (TCI) approaches. The research methodology employs a quantitative-descriptive approach with secondary data from BPS, UN Comtrade, ITC Trade Map, and Bank Indonesia for the period 2020–2025. The results indicate that Indonesia has significant export opportunities in the Indian market, particularly in electronics, crude palm oil (CPO), fishery products, and textiles. However, Indonesia faces challenges including a low RCA value for electronics products (0.28), intense competition from China and Vietnam, and tariff barriers within the ASEAN-India FTA framework. This study recommends strengthening competitiveness through fiscal incentives, diversification of export products, and accelerating bilateral trade agreements. These findings contribute to international trade literature in the context of Indonesia–South Asia relations.